2021
DOI: 10.1007/s10353-021-00704-0
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of traumatic and non-traumatic lower extremity defects with local or free flaps

Abstract: Summary Background Despite continuous surgical advances, reconstruction of complex lower extremity wounds remains challenging. The indication of local flaps or microsurgical free tissue transfer depends on the anatomical location and size of the defect, as well as the comorbidities and general condition of the patient. In this study, local and free flap reconstruction of distal lower extremity defects was assessed, and postoperative complications and limb salvage were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Defect aetiology varied greatly between and inside the selected studies including traumatism, neoplasm, infections, scar contractures, and chronic wounds (with peripheral vascular disease, irradiation, and neuropathy). Complete flap necrosis was reported in all 10 articles and the pooled analysis did not find a significant difference between FF and PF (RR 1.35, 95%CI 0.76-2.39, p = 0.31) [12][13][14][15][16][17][18][19][20][21]. (Figure 2) A partial flap failure was reported in eight articles and FF had a significantly lower risk than PF in the pooled analysis (RR 0.45, 95%CI 0.22-0.91, p = 0.03) [12][13][14][15][16][18][19][20] (Figure 3).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Defect aetiology varied greatly between and inside the selected studies including traumatism, neoplasm, infections, scar contractures, and chronic wounds (with peripheral vascular disease, irradiation, and neuropathy). Complete flap necrosis was reported in all 10 articles and the pooled analysis did not find a significant difference between FF and PF (RR 1.35, 95%CI 0.76-2.39, p = 0.31) [12][13][14][15][16][17][18][19][20][21]. (Figure 2) A partial flap failure was reported in eight articles and FF had a significantly lower risk than PF in the pooled analysis (RR 0.45, 95%CI 0.22-0.91, p = 0.03) [12][13][14][15][16][18][19][20] (Figure 3).…”
Section: Resultsmentioning
confidence: 88%
“…Complete flap necrosis was reported in all 10 articles and the pooled analysis did not find a significant difference between FF and PF (RR 1.35, 95%CI 0.76-2.39, p = 0.31) [12][13][14][15][16][17][18][19][20][21]. (Figure 2) A partial flap failure was reported in eight articles and FF had a significantly lower risk than PF in the pooled analysis (RR 0.45, 95%CI 0.22-0.91, p = 0.03) [12][13][14][15][16][18][19][20] (Figure 3). Overall complication rates were reported in six studies, and the pooled analysis found no significant difference between FF and PF concerning the overall risk of complications (RR 0.83, 95%CI 0.64-1.07, p = 0.16) [13,15,16,[19][20][21] (Figure 4).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations